2023
DOI: 10.21468/scipostphys.15.1.016
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional points in the Baxter-Fendley free parafermion model

Abstract: Certain spin chains, such as the quantum Ising chain, have free fermion spectra which can be expressed as the sum of decoupled two-level fermionic systems. Free parafermions are a generalisation of this idea to \mathbb{Z}_NℤN-symmetric clock models. In 1989 Baxter discovered a non-Hermitian but \mathcal{PT}𝒫𝒯-symmetric model directly generalising the Ising chain, which was later described by Fendley as a free parafermion spectrum. By extending the model’s magnetic field parameter to the complex plane, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…also a more recent review of the field in [41]). In essence, the latter authors revealed that in a number of specific toy models the conventional ansatz (45) may still serve as a productive constructive tool, yielding, at the small and real coupling constants, the real (i.e., energy-like) as well as complex (i.e., resonance-representing) lowlying spectra after standard resummation.…”
Section: A Detour To Meaningful Complex Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…also a more recent review of the field in [41]). In essence, the latter authors revealed that in a number of specific toy models the conventional ansatz (45) may still serve as a productive constructive tool, yielding, at the small and real coupling constants, the real (i.e., energy-like) as well as complex (i.e., resonance-representing) lowlying spectra after standard resummation.…”
Section: A Detour To Meaningful Complex Spectramentioning
confidence: 99%
“…The reality of spectra of the Hamiltonians has independently been noticed in the context of quantum field theory [12]. This attracted the attention of the physics community to the applicability of expansions (45) in the non-Hermitian setting of Equation (44). The authors of the innovated studies of imaginary cubic anharmonic-oscillator Hamiltonians…”
Section: Real Spectra and The Paradox Of Emergent Instabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A Jordan-Wigner-like transformation [4], unlike in the TFIC, does not make this task at all trivial: the aforementioned parafermionic operators are highly nonlinear in these Jordan-Wigner parafermions. While a number of observables in the homogeneous (J j = J, h j = h for all j) version of the model, especially in the vicinity of h = J, have been calculated [5][6][7][8][9][10][11], the fact that the model is in principle exactly solvable for inhomogeneous couplings has not been exploited. This is the goal of the present paper.…”
Section: Introductionmentioning
confidence: 99%